Assessment and management of connective tissue disease-associated interstitial lung disease - Fischer, Aryeh; Chartrand, Sandra (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
The intersection of the connective tissue diseases (CTD) and the interstitial lung diseases (ILD) is complex. Although often considered as a single entity, “CTD-ILD” actually reflects a heterogeneous spectrum of diverse CTDs and a variety of patterns of interstitial pneumonia. The evaluation of patients with CTD that develop ILD, or the assessment for underlying CTD in those presenting with presumed “idiopathic” ILD can be challenging and these evaluations can be optimized by effective multidisciplinary collaboration. When a diagnosis of CTD-ILD is confirmed, careful and thorough assessments to determine extra- versus intra-thoracic disease activity, and degrees of impairment are needed. Pharmacologic intervention with immunosuppression is the mainstay of therapy for all forms of CTD-ILD, but should be reserved only for those that demonstrate clinically significant and/or progressive disease. The management of CTD-ILD is not yet evidence based and there is a desperate need for controlled trials across the spectrum of CTD-ILD. Non-pharmacologic management strategies and addressing comorbidities or aggravating factors should be part of a comprehensive treatment plan for individuals with CTD-ILD.